Enrichment of Refined Olive Oils with Phenolic Extracts of Olive Leaf and Exhausted Olive Pomace - Alfonso M. Vidal; Manuel Moya; Sonia Alcalá; Inmaculada Romero; Francisco Espínola (Antioxidants, 2022)
Refined olive oils (ROOs) are commonly enriched with synthetic antioxidants. Antioxidant extracts obtained from natural products can be used to improve the stability of these oils. In this study, ROOs were enriched through the addition of phenolic extracts from olive leaves (OLs) and exhausted olive pomace (EOP). In addition to replacing synthetic antioxidants with natural ones, this results in the valorization of these olive-derived biomasses. The most suitable method for mixing and enriching refined oils was probe-type ultrasonication using lecithin as the emulsifier. Thereafter, the change in the content of antioxidant compounds and the antioxidant capacity of the oils at 25, 35, and 45 °C were studied over 28 and 50 days of storage. The experimental results were fitted using a pseudo-first-order kinetic model. The oxidative stability index of the ROO enriched with a 2 g/L OL extract (70 h) was higher than that of a commercial ROO (46.8 h). Moreover, the oxidative stability index of the refined olive pomace oil (ROPO) enriched with a 2 g/L EOP extract (44.1 h) was higher than that of a commercial ROPO (38.9 h). In addition, the oxidative stabilities and antioxidant capacities of the oils were significantly correlated.